Leveraging the OpenAIRE Graph for Transparent and Responsible Research Assessment (PUBMET, 2025)
A key element of Reforming Research Assessment (RRA) practices is to move away from simplistic approaches based on bibliometric indicators and consider a wide variety of research activities. Existing large-scale data collections cover a broader range of research output such as publications, data, software, research methods, patents, data management plans and tools. The current challenge is the lack of a robust, high-quality open infrastructure.
Keywords: monitoring; indicators; OpenAIRE Graph; open infrastructures; Open Science policies; reforming research assessment